Impactos na ergonomia organizacional do ambiente produtivo causados pelo absenteismo- estudo de caso em uma indústria de alimentos do noroeste de Santa Catarina - Flores, Kessy de Avila (2024)
Absenteeism is one of the critical factors that can have profound impacts on companies, especially when linked to organizational ergonomics. The workplace is often marked by a variety of organizational issues that affect business dynamics. This study aims to identify the effects of absenteeism in a food industry in northwest Santa Catarina, analyzing how these impacts relate to organizational ergonomics. Using the Proknow-C methodology for the selection and analysis of journals, the study explored the processes, groups, and variables most affected between 2018 and 2022. The goal is to provide effective management parameters to address unplanned absences, integrating actions aligned with ergonomic principles in the workplace. With a clearly defined temporal and population focus, the research concentrates on food production, excluding areas such as administration. The scientific relevance of this study lies in its contribution to the development of occupational health management policies and workload studies, while its social importance lies in generating indicators that can guide project planning, improve team training, and increase industrial. The data collected will be treated statistically to deepen studies and compare with research already carried out by other authors. The study analyzed the impact of absenteeism between 2018 and 2022, focusing on biscuit production lines, with the afternoon shift being the most affected. The main causes of absenteeism were low back pain, gastrointestinal infections, and coronavirus, exacerbated by the pandemic. Additionally, issues such as employee turnover, presenteeism, and workload overload were identified. Suggestions to mitigate these factors include implementing attendance awards, improving working conditions, training leaders, and restructuring positions and salaries.